2021
DOI: 10.7759/cureus.17814
|View full text |Cite
|
Sign up to set email alerts
|

Patient Satisfaction With Remote Consultations in a Primary Care Setting

Abstract: In recent years, the use of remote consultations has increased considerably. Many patient encounters in general practice are now conducted by phone or computer as opposed to traditional face-to-face appointments. The aim of this study was to measure patient satisfaction with remote consultations in a primary care setting. AimsTo assess patient satisfaction with telephone consultations in a general practice setting and explore patient's experiences and attitudes toward remote consultations in general practice t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 17 publications
(36 reference statements)
3
17
0
3
Order By: Relevance
“… 25 COVID-19 pandemic factors such as lack of continuity of care, inadequate information, and difficulty accessing health care may also have contributed to this overall increase. 25 30 The finding in the current study of a positive association between travel time to GP and an increase in treatment burden is consistent with findings from qualitative studies on the time burden associated with travel to health care. 31 , 32 This association was moderated by health literacy, in line with studies suggesting health literacy may be protective against experiencing high treatment burden.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“… 25 COVID-19 pandemic factors such as lack of continuity of care, inadequate information, and difficulty accessing health care may also have contributed to this overall increase. 25 30 The finding in the current study of a positive association between travel time to GP and an increase in treatment burden is consistent with findings from qualitative studies on the time burden associated with travel to health care. 31 , 32 This association was moderated by health literacy, in line with studies suggesting health literacy may be protective against experiencing high treatment burden.…”
Section: Discussionsupporting
confidence: 87%
“…[24] For some, the lack of social support or reduced contact with a health professional may have increased treatment burden. [25][26][27][28][29][30] Surveys were mailed out at a point of minimal COVID restrictions to try and minimise these effects. Secondly, although exceeding the minimum target sample size, the study may have been underpowered to assess some associations with treatment burden category change and the clinical significance of a single point change in MTBQ global score has not been well established.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…We found that in all studies remote consultations were found to improve the quality of patient care ( 24 ), the effects on patients were strongly positive ( 26 ) and thus it can be an effective replacement for physical consultations or home visits ( 25 ). Patients also agree that they are an effective complement to physical consultation, and believed that this approach improves the quality of care.…”
Section: Discusionmentioning
confidence: 99%
“…This technology has enabled care for patients from a safe distance, and has created an opportunity to organize work in GPs’ offices differently ( 7 ). The studies used a variety of telehealth tools, such as consultation by mail ( 15 , 19 , 20 , 21 ), by telephone ( 17 ), by video call ( 18 ) or various combinations of these ( 16 , 22 , 23 , 24 , 25 , 26 ). We established in our review that teleconsultations can reduce the number of visits ( 21 ).…”
Section: Discusionmentioning
confidence: 99%
“…Patients share these concerns, feeling greater anxiety and worrying about whether they can effectively convey their symptoms to the clinician. 29 Our evaluation reflects these concerns specifically in terms of clinician fears about patients ‘getting lost in the system’, security, privacy and safeguarding whilst patients voiced concerns about missed diagnoses and finding the language to communicate their symptoms.…”
Section: Discussionmentioning
confidence: 99%